2015
DOI: 10.1016/j.bbrc.2015.08.026
|View full text |Cite
|
Sign up to set email alerts
|

Lipoprotein lipase is an important modulator of lipid uptake and storage in hypothalamic neurons

Abstract: LPL is the rate-limiting enzyme for uptake of TG-derived FFA in peripheral tissues, and the enzyme is expressed in the brain and CNS. We previously created a mouse which lacks neuronal LPL. This animal becomes obese on a standard chow, and we observed reduced lipid uptake in the hypothalamus at 3 months preceding obesity. In our present study, we replicated the animal phenotype in an immortalized mouse hypothalamic cell line (N41) to examine how LPL affects expression of AgRP as well as entry and storage of li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 27 publications
2
16
0
Order By: Relevance
“…In our mouse model, we also found changes in AGRP immunoreactivity in the hypothalamus that might be a consequence of reduced lipid storage in the microenvironment as a result of the LPL deletion in astrocytes. Indeed, Libby et al (34) reported that LPL is able to modulate AGRP level by regulating lipid storage in neurons. In addition to ceramide-induced lipid toxicity, we also observed elevation of ER stress markers and increased microglial immunoreactivity in the hypothalamus, both of which are associated with ceramide accumulation, as reported in other studies (31,32).…”
Section: Discussionmentioning
confidence: 99%
“…In our mouse model, we also found changes in AGRP immunoreactivity in the hypothalamus that might be a consequence of reduced lipid storage in the microenvironment as a result of the LPL deletion in astrocytes. Indeed, Libby et al (34) reported that LPL is able to modulate AGRP level by regulating lipid storage in neurons. In addition to ceramide-induced lipid toxicity, we also observed elevation of ER stress markers and increased microglial immunoreactivity in the hypothalamus, both of which are associated with ceramide accumulation, as reported in other studies (31,32).…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, we have recently shown that lipoprotein lipase (LPL), the rate-limiting enzyme in the hydrolysis of lipoprotein-derived FAs, may facilitate the uptake of FAs into dissociated hypothalamic neurons (39). Moreover, mice with a specific neuronal LPL deficiency exhibit a defect in nutrient sensing and become hyperphagic, relatively inactive and obsessed compared to WT control mice (40).…”
Section: Neuronal Uptake Of Lipids and Fasmentioning
confidence: 99%
“…For example, hypothalamic lipoprotein lipase, which promotes lipid uptake by hypothalamic neurons, has been demonstrated to enhance brain lipid sensing and to play a role in the regulation of energy balance [141,142] . Angiopoietin-like protein 3 significantly stimulates hypothalamic lipoprotein lipase activity, exhorting anorexia and weight loss, a mechanism which could be induced or commanded by leptin [143,144] .…”
Section: From Hypothalamic Lipid Metabolism To Whole Body Energy Homementioning
confidence: 99%